The Analysis of Approaches to Low Carbon Tourism Management in Thailand by Using Koh Mak Island, Trat Province as a Case Study - Laowirojanakul, Thareethip; Sangpikul, Aswin (Academic and Research Journal of Liberal Arts (Online), 2024)
The objectives of this study are to 1) examine the components of low-carbon tourism from academic sources 2) examine the practical management of low-carbon tourism in the Koh Mak Island area, Trat province, based on data from various media sources and 3) to analyze and determine suitable management strategies for the low-carbon tourism in Thailand. This study collected data from 2 sources: a) academic sources from the TCI database and Google Scholar and b) media sources presenting information about low-carbon tourism in Koh Mak Island, using content analysis to analyze the data. The study found that 1) the components of carbon tourism from academic sources were summarized and synthesized into 8 components: low-carbon communities, low-carbon tourist attractions, low-carbon accommodations, low-carbon food, low-carbon activities, low-carbon transportation, network cooperation, and publicity. 2) The management of the low carbon tourism in Koh Mak Island, Trat province was categorized into 9 components. The 1st – 8th components were similar to the first finding while the 9th was energy management. 3) The analysis of approaches of low carbon tourism management in Thailand through integrating the first and second findings was derived 9 concepts. The current study is expected to fulfill the body of knowledge regarding low-carbon tourism that communities and relevant organizations can apply to enhance and develop low-carbon tourism management. These strategies aim to promote effective management practices for low-carbon tourism in Thailand, fostering sustainability for the future.